The Mouse Woman of Gabriola - Young, David E. (Religious studies and theology, 2011)
The Mouse Woman of Gabriola is an image carved into a boulder on the small island of Gabriola, off the west coast of Canada. The "grandmother" spirit depicted in the image is important to west coast native groups who believe that this spirit is dedicated to restoring order and rectifying injustices, particularly those involving young people. The Mouse Woman also appears to have healing powers that defy normal scientific explanation. This article attempts to understand this type of "spontaneous healing" by exploring factors such as the role of healers, the role of faith, mind/brain/body interactions, the placebo response, the ability of individuals to tap internal and external sources of healing energy, and the role of religious icons in healing. The arguments made in this article will come as no surprise to most Aboriginal medicine people who are quite aware that a healer must have a good understanding of not only plants and their medicinal qualities, but human psychology, the power of suggestion and ritual, and even the worth of dramatic elements. Thus traditional healers are often more sophisticated than mainstream medical researchers who have only recently begun to appreciate the significance of phenomena such as role of the mind in healing.